Study of Cu-doped zirconia toughened alumina ceramics (Cu-ZTA) subject to lubrication behaviors for arthroplasty - Li, Y.X.; Gong, Y.L.; Li, Q.; Xiang, Y.; Li, S.; Leng, Y.X. (Ceramics international, 2024)
Zirconia-toughened alumina (ZTA) is widely applied in total hip arthroplasty (THA). However, problems with insufficient fracture toughness and lubrication remain, leading to wear, squeaking, and fracturing. In this study, the Cu doping of ZTA (Cu-ZTA) is proposed to solve these problems. To further promote the use of Cu-ZTA, the role of Cu doping on its tribological properties must be studied. In this study, the microstructure, mechanical properties, and stability capacity in a physiological environment, as well as the tribological behaviors of Cu-ZTA in phosphate-buffered saline (PBS) and bovine serum albumin (BSA), were systematically studied with varying amounts of Cu. The results demonstrated that holes and soft Cu-rich phases appeared, and grains grew after Cu doping, causing a decrease in hardness. The fracture toughness increased after Cu doping because the Cu-rich particles formed “bridges” during crack propagation and release energy. The incorporation of Cu improved the stability of ZTA in physiological environments, which enhanced the long-term stability of Cu-ZTA. The protein adsorption results indicated that a higher hydrophobicity and roughness contributed to a greater protein adsorption on the Cu-ZTA surfaces after Cu incorporation. In the BSA solution, the 5.0 wt% Cu-ZTA ceramics achieved a lower coefficient of friction (COF) and wear rate compared to ZTA, and a higher protein adsorption and formation of the denatured protein layer catalyzed by Cu ions in the wear track during friction, thus clearly improving the tribological properties of the Cu-ZTA.